2017
DOI: 10.1371/journal.pone.0182282
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between p-STAT3 overexpression and prognosis in lung cancer: A systematic review and meta-analysis

Abstract: ObjectivePrevious studies have shown the correlation between p-STAT3 overexpression and prognosis in a variety of human tumors. However, their correlation in lung cancer remains controversial. We performed a systematic review and meta-analysis to explore the correlation between p-STAT3 overexpression and prognosis in lung cancer patients.MethodsWe searched PubMed, Embase, Web of Science, CNKI, VIP, and WanFang Data to identify relevant studies. Two reviewers independently screened the literature search results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…STATs regulate the expression of genes, which they are involved in cell growth and division. It was observed that over expression of STAT3 has bad prognosis in lung (Tong, Wang, Jiang, Pan, & Li, ) and pancreatic (C. Huang et al, ) cancers and so increased cancer cells survival and proliferation. Interleukin (IL) 6 that has a major role in STAT3 activation is one of the crucial cytokines in the tumor microenvironment that is detected at extraordinary concentrations in cancer.…”
Section: Flavonoids Functional Mechanisms In Leukemia Cellsmentioning
confidence: 99%
“…STATs regulate the expression of genes, which they are involved in cell growth and division. It was observed that over expression of STAT3 has bad prognosis in lung (Tong, Wang, Jiang, Pan, & Li, ) and pancreatic (C. Huang et al, ) cancers and so increased cancer cells survival and proliferation. Interleukin (IL) 6 that has a major role in STAT3 activation is one of the crucial cytokines in the tumor microenvironment that is detected at extraordinary concentrations in cancer.…”
Section: Flavonoids Functional Mechanisms In Leukemia Cellsmentioning
confidence: 99%
“…The JAK-STAT pathway is one of the most studied pathways in cellular signal transduction with diverse roles in physiological processes including cell growth and differentiation and immune response via cytokine signalling [9]. Dysregulations in this pathway are implicated in carcinogenesis and are also associated with poor prognosis in various cancers including kidney cancer [10], lung cancer [11], cervical cancer [12] and bladder cancer [13,14]. The JAK (Janus Kinase) protein family consists of JAK1-3 and Tyk2 in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 protein is 1 of 7 cytoplasmic transcription factor family members including STAT1-6, STAT5a, and STAT5b ( Furqan et al, 2013 ) which are aberrantly activated in lung cancer tissues ( Sanchez-Ceja et al, 2006 ; Jiang et al, 2016 ). Moreover, increased STAT3 activity is correlated to poorer overall survival of lung cancer patients ( Tong et al, 2017 ). Thus, STAT3 has been regarded as a key target for lung cancer prevention ( Dutta et al, 2014 ; Harada et al, 2014 ), and inhibition of STAT3 signal showed great anticancer and antiangiogenic effects in vitro and in vivo ( Yang et al, 2012 ; Xu and Zhu, 2017 ).…”
Section: Introductionmentioning
confidence: 99%